2008
DOI: 10.2193/2005-521
|View full text |Cite
|
Sign up to set email alerts
|

Population Ecology of the Eastern Box Turtle in a Fragmented Landscape

Abstract: In the mid‐Atlantic region, urban sprawl and development have resulted in habitat alterations and fragmentation; however, the effects on eastern box turtle (Terrapene carolina carolina) populations are unclear. To investigate the status of eastern box turtle populations in a fragmented landscape, we used mark—recapture and radiotelemetry to estimate population density, sex ratio, age structure, and survival on 4 study areas with differing degrees of isolation and human disturbance in northern New Castle County… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 19 publications
6
52
0
Order By: Relevance
“…Our estimates of box turtles per area were similar to some of these past studies (Williams and Parker 1987;Quinlan et al 2003Quinlan et al /2004Nazdrowicz et al 2008), and substantially lower than others (e.g., Boucher 1999; Wilson and Ernst 2005;Langtimm et al 1996).…”
Section: Numerous Past Studies Have Estimated Eastern Boxsupporting
confidence: 88%
See 1 more Smart Citation
“…Our estimates of box turtles per area were similar to some of these past studies (Williams and Parker 1987;Quinlan et al 2003Quinlan et al /2004Nazdrowicz et al 2008), and substantially lower than others (e.g., Boucher 1999; Wilson and Ernst 2005;Langtimm et al 1996).…”
Section: Numerous Past Studies Have Estimated Eastern Boxsupporting
confidence: 88%
“…Results of surveys at two locations in Virginia provided estimates of 23.8 turtles/ha and 16 turtles/ha (Boucher 1999;Wilson and Ernst 2005, respectively). Nazdrowicz et al (2008) reported 0.81-3.56 turtles/ha across four study sites in Delaware.…”
Section: Numerous Past Studies Have Estimated Eastern Boxmentioning
confidence: 99%
“…Females of other box turtle subspecies often multi-clutch within a single season with clutch fertility varying from 0% to 95% [5]. Among these subspecies, few hatchlings survive to adulthood and females likely require decades to replace the adults in a population [2,13,43]. In addition to these reproductive hurdles, the means of finding mates appears to be a fundamentally random event [2,13].…”
Section: Introductionmentioning
confidence: 99%
“…Male‐biased sex ratios have been further documented more recently in nonmarine turtles (Edmonds and Brooks ; Dodd ; Hailey and Willamsen ; Smith and Iverson ; Nazdrowicz et al. ), crocodilians (Platt et al. ), tuataras (Grayson et al.…”
Section: Discussionmentioning
confidence: 89%
“…Reviews of the ESD taxon with the next most available sex ratio data, the Crocodilia, similarly found more than twice as many male biases as female biases (Nichols and Chabrek 1980;Thorbjarnarson 1997;Lance et al 2000), with no evidence of early maturation of males that can explain this result. Male-biased sex ratios have been further documented more recently in nonmarine turtles (Edmonds and Brooks 1996.;Dodd 1997;Hailey and Willamsen 2000;Smith and Iverson 2002;Nazdrowicz et al 2008), crocodilians (Platt et al 2009), tuataras (Grayson et al 2014), and copepods (Voordouw and Anholt 2002).…”
Section: Are Esd Sex Ratios Male-biased?mentioning
confidence: 94%